PEMETAAN TEMA: UPAYA MENEMUKAN PELUANG BARU PENELITIAN PEDAGANG KAKI LIMA (PKL - Pranata, Albertus Adhipuspa; Purbadi, Yohanes Djarot (Jurnal Arsitektur Komposisi, 2020)
The purpose of this article is to find and formulate new research opportunities for street vendors (PKL). Street vendors have become an integral part of urban space and life in Indonesia and various cities in the world. Many types of research have been done on street vendors and spread in scientific journal articles. The object of this research is a scientific journal article that contains street vending research themes in Indonesia and abroad. The method used is the search and mapping of research themes about street vendors purposively, gathering information in scientific journal articles, and systematizing to obtain key ideas in formulating a map of PKL research opportunities. As a result, there are many opportunities in the form of themes and research focus on street vendors found, especially related to the interests of public space. Opportunities for the theme of street vendors research related to key ideas of food and non-food street vendors, migrant street vendors, night and  day  street  vendors, permanent street  vendors, and  specifically focused on  targets regarding characteristics, transformation, and attachment of places among street vendors.